2011
DOI: 10.1017/s175173111100111x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling as a tool to redesign livestock farming systems: a literature review

Abstract: Livestock farming has recently come under close scrutiny, in response especially to environmental issues. Farmers are encouraged to redesign their livestock farming systems in depth to improve their sustainability. Assuming that modelling can be a relevant tool to address such systemic changes, we sought to answer the following question: 'How can livestock farming systems be modelled to help farmers redesign their whole farming systems?' To this end, we made a literature review of the models of livestock farmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 105 publications
0
23
0
2
Order By: Relevance
“…The second type of analysis is performed through a participatory approach aiming to collectively construct conceptual representations of the functioning of farming systems, supply chains and natural resource management and their interactions. To perform this co-construction, we use methods for collective construction of cognitive maps, such as those representing farming system functioning (Gouttenoire et al 2011), natural resource management at the local level (Etienne et al 2008) and social-ecological system functioning (Sibertin-Blanc et al 2011). The final objective of this step is to compare the social interactions that determine the functioning of local agriculture and natural resource management mapped by both approaches and, ultimately, for stakeholders and researchers to build them into a new shared representation.…”
Section: A Five-step Methodologymentioning
confidence: 99%
“…The second type of analysis is performed through a participatory approach aiming to collectively construct conceptual representations of the functioning of farming systems, supply chains and natural resource management and their interactions. To perform this co-construction, we use methods for collective construction of cognitive maps, such as those representing farming system functioning (Gouttenoire et al 2011), natural resource management at the local level (Etienne et al 2008) and social-ecological system functioning (Sibertin-Blanc et al 2011). The final objective of this step is to compare the social interactions that determine the functioning of local agriculture and natural resource management mapped by both approaches and, ultimately, for stakeholders and researchers to build them into a new shared representation.…”
Section: A Five-step Methodologymentioning
confidence: 99%
“…This has led various authors to highlight the need for incorporating social aspects into DSS (Edwards-Jones, 2006;Gouttenoire et al, 2011). In order to improve decision-making in social-ecological systems, greater understanding is needed of the knowledge used by managers (such as farmers) in managing their systems (Girard and Hubert, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, Moloney and Hearne (2009) showed that the replacement of domestic livestock with native alternatives, or even mixed grazing, is economically and environmentally viable. The interested reader can find a review of optimisation and simulation models of livestock farming systems with emphasis in sustainability in Gouttenoire et al (2011).…”
Section: Sustainabilitymentioning
confidence: 99%